Substitutional Vanadium Sulfide Nanodispersed in MoS2 Film for Pt‐Scalable Catalyst. Issue 16 (3rd June 2021) - Agyapong‐Fordjour, Frederick Osei‐Tutu; Yun, Seok Joon; Kim, Hyung‐Jin; Choi, Wooseon; Kirubasankar, Balakrishnan; Choi, Soo Ho; Adofo, Laud Anim; Boandoh, Stephen; Kim, Yong In; Kim, Soo Min; Kim, Young‐Min; Lee, Young Hee; et al.
Abstract: Among transition metal dichalcogenides (TMdCs) as alternatives for Pt‐based catalysts, metallic‐TMdCs catalysts have highly reactive basal‐plane but are unstable. Meanwhile, chemically stable semiconducting‐TMdCs show limiting catalytic activity due to their inactive basal‐plane. Here, metallic vanadium sulfide (VS n ) nanodispersed in a semiconducting MoS2 film (V–MoS2 ) is proposed as an efficient catalyst. During synthesis, vanadium atoms are substituted into hexagonal monolayer MoS2 to form randomly distributed VS n units. The V–MoS2 film on a Cu electrode exhibits Pt‐scalable catalytic performance; current density of 1000 mA cm −2 at 0.6 V and overpotential of −0.08 V at a current density of 10 mA cm −2 with excellent cycle stability for hydrogen‐evolution‐reaction (HER). The high intrinsic HER performance of V–MoS2 is explained by the efficient electron transfer from the Cu electrode to chalcogen vacancies near vanadium sites with optimal Gibbs free energy (−0.02 eV). This study provides insight into ways to engineer TMdCs at the atomic‐level to boost intrinsic catalytic activity for hydrogen evolution. Abstract : The nanodispersed vanadium sulfide (VS n ) in the MoS2 lattice is key for efficient hydrogen evolution by increasing the electrical conductivity and basal plane activity of V–MoS2 catalyst. The engineering advantage is that the stability of VS2 is ensured by the embedded VS n in MoS2 and the copper substrate tunes the Gibbs free energy and facilitates electron injection to active sites.